Ki‐67, mini‐chromosome maintenance 2 protein (MCM2) and geminin have no independent prognostic relevance for cancer‐specific survival in surgically treated squamous cell carcinoma of the penis. (10th January 2013) - May, Matthias; Burger, Maximilian; Otto, Wolfgang; Hakenberg, Oliver W.; Wieland, Wolf F.; May, Dieter; Hofstädter, Ferdinand; Götz, Stefanie; Niessl, Nina; Fritsche, Hans‐Martin; Birnkammer, Kristina; Gilfrich, Christian; et al.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Only little and partly contradictory data are currently published about the prognostic role of immunohistochemically detectable proliferation‐associated biomarkers in surgically treated squamous cell carcinoma of the penis (SCCP), and no data are available at present about their usefulness for refining the delineation between different Broders' grading categories (e.g. still G2 or just G3 SCCP?). Moreover, the accuracy of various conventional histopathological parameters for predicting cancer‐specific survival (CSS) in surgically treated SCCP has not been systematically evaluated yet. Based on the so far largest study cohort encompassing 158 consecutive patients with surgically treated PSCCs characterised by means of a central histopathological review, our data add the following to the currently available literature: (i) Ki‐67, mini‐chromosome maintenance 2 protein (MCM2), and geminin indicate a more aggressive behaviour in SCPP but do not represent independent prognostic parameters in the multivariable analysis in terms of CSS, (ii) these three biomarkers are not helpful for refining the delineation between different Broders' grading categories at the immunohistochemical level, and (iii) the conventional histopathological parameters staging, grading, nodal involvement, and lymphovascular invasion are independent prognostic parameters that together achieve a predictive accuracy of 82% for CSS. Objective To assess the role of cell proliferation‐associated biomarkers to predict cancer‐specific survival (CSS) in patients with surgically treated squamous cell carcinoma of the penis (SCCP). Patients and Methods A multicentre study enrolling 158 consecutive patients with surgically treated SCCP was performed. After conducting a central histopathological review, the staining profiles of Ki‐67, mini‐chromosome maintenance 2 protein (MCM2) and geminin were evaluated for their correlation with conventional histopathological criteria and their prognostic relevance for predicting CSS in a multivariable Cox proportional hazards regression model (median [interquartile range] follow‐up 33 [6–63] months). Results Staining evaluation showed high interobserver agreement (92–96%). Ki‐67 and MCM2 displayed a significant positive correlation with histological tumour grade, lymphovascular invasion (LVI) and nodal status, whereas geminin expression only correlated with tumour grade. The 5‐year CSS for the entire study cohort was 62%. Univariable analysis showed a significant prognostic impact of Ki‐67 (P = 0.026), MCM2 (P = 0.007), and geminin (P = 0.036). In multivariable analysis, only pT (hazard ratio [HR] 1.67; P = 0.003) and pN stage (HR 2.62; P = 0.015) as well as tumour grade (HR 1.89; P = 0.036) and LVI (HR 2.66; P = 0.028) were identified as independent prognostic parameters for CSS. The accuracy of the Cox model for CSS prediction was 0.820 (95% confidence interval 0.741–0.898). Conclusions At present, conventional histopathological criteria remain the most powerful predictors of CSS in surgically treated SCCP. Due to overlapping staining profiles, Ki‐67, MCM2 and geminin, either singly or in various combinations, failed to immunohistochemically refine the boundaries between Broders' grading categories. Ki‐67, MCM2 and geminin do not represent independent prognostic parameters but reflect a more aggressive behaviour in surgically treated SCCP. Further studies are needed to clarify the currently contradictory predictive role of proliferation‐associated biomarkers in terms of predicting nodal involvement in SCCPs.